The Structure of Compound Sentence in Sulaimani Sub Dialect - Hussin, Azad A. (Humanities Journal of University of Zakho, 2018)
This paper which is entitled “The structure of compound sentence in Sulaimani sub dialect”. In Kurdish grammar, only one type of compound sentence is mentioned which is composed of two simple sentences. The simple sentences have the same grammatical value. This is one way of constructing a compound sentence, yet there is more than one way to do this. This paper is an attempt to demonstrate the methods of constructing compound sentences. It shows three other ways to produce a compound sentence apart from what Kurdish grammarians and linguists have already mentioned. The proposed methods are: Two phrases or more are joined by a coordinating conjunctive ‘و’. A compound sentence by exceptional. A compound sentence by the verb complements ‘بوو’ when it is a comparative adjectival phrase. Every compound sentence constructed by using any of the above mentioned methods can be changed to another form of compound sentence composed of two or more simple sentences.